Differential expression of plasma extracellular vesicles microRNAs and exploration of their association with bone metabolism in childhood trauma participants treated in a psychosomatic clinic - He, Yangyang; Wuertz-Kozak, Karin; Cazzanelli, Petra; Houtenbos, Sanne; Garcia-Carrizo, Francisco; Schulz, Tim J.; Wippert, Pia-Maria (Frontiers in Endocrinology, 2025)
IntroductionEarly life stress (ELS) impacts neurotransmitters and cell communication, potentially disrupting neurological and physiological processes. Recently, ELS has been implicated in impaired bone metabolism, with extracellular vesicles (EVs) and their cargo, microRNAs (miRNAs), might affecting this process. This research aimed to elucidate the association between childhood trauma, a specific form of ELS, and bone metabolism through studying miRNA in EVs within three steps: firstly, examining alterations of EV miRNAs between ELS and controls, secondly analyzing associations between altered EV miRNAs and bone markers, and thirdly exploring the target gene prediction and enrichment pathways of altered EV miRNAs.MethodsThis study included a subgroup of the DEPREHA project (total n=208) from a psychosomatic clinic. Firstly, real-time quantitative PCR was performed on plasma EVs isolated from childhood trauma participants with depression (n=6) and matched healthy controls (n=9) to detect the differentially expressed EV miRNAs. Secondly, general linear regression models were employed to investigate the associations between specific EV miRNAs and circulating bone turnover markers (procollagen type 1 amino-terminal propeptide (P1NP), osteocalcin, and β-CrossLaps (CTx)), adjusting for depression as a potential confounder. Thirdly, the miRNA target gene networks and enriched pathways were explored based on altered EV miRNAs.ResultsThese analyses could be conducted on n=19 participants from the entire group (11 [57.9%] female; median [IQR] age, 35.00 [26.00] years), but finally n=15 participants were included for analyses. 22 out 380 EV miRNAs were differentially expressed between childhood trauma participants (6 up-regulated and 16 down-regulated) and healthy controls. Among these, miR-25-3p, miR-26b-5p, miR-451a, and miR-421 were associated with P1NP (bone formation marker) and CTx (bone resorption marker). MiR-26b-5p, miR-330-3p, and miR-542-5p were associated with osteocalcin (bone turnover marker). MiRNA target gene network prediction revealed highly associated target genes of dysregulated miRNAs, such as Trinucleotide Repeat Containing Adaptor 6B (TNRC6B), and enrichment analysis highlighted pathways including the forkhead box protein O (FoxO) signaling pathway.DiscussionsThis study explored the potential associations between childhood trauma and bone metabolism, due to the sample size and experimental group limitations, these associations should be validated in future experiments with larger sample sizes and different control group settings.